K‐29 linked ubiquitination of Arrdc4 regulates its function in extracellular vesicle biogenesis. Issue 2 (1st February 2022) - Farooq, Ammara Usman; Gembus, Kelly; Sandow, Jarrod J.; Webb, Andrew; Mathivanan, Suresh; Manning, Jantina A.; Shah, Sonia S.; Foot, Natalie J.; Kumar, Sharad
Abstract: Extracellular vesicles (EVs) are important mediators of intercellular communication. However, EV biogenesis remains poorly understood. We previously defined a role for Arrdc4 (Arrestin domain containing protein 4), an adaptor for Nedd4 family ubiquitin ligases, in the biogenesis of EVs. Here we report that ubiquitination of Arrdc4 is critical for its role in EV secretion. We identified five potential ubiquitinated lysine residues in Arrdc4 using mass spectrometry. By analysing Arrdc4 lysine mutants we discovered that lysine 270 (K270) is critical for Arrdc4 function in EV biogenesis. Arrdc4 K270R mutation caused a decrease in the number of EVs released by cells compared to Arrdc4 WT, and a reduction in trafficking of divalent metal transporter (DMT1) into EVs. Furthermore, we also observed a decrease in DMT1 activity and an increase in its intracellular degradation in the presence of Arrdc4 K270R . K270 was found to be ubiquitinated with K‐29 polyubiquitin chains by the ubiquitin ligase Nedd4‐2. Thus, our results uncover a novel role of K‐29 polyubiquitin chains in Arrdc4‐mediated EV biogenesis and protein trafficking.